Differences in the rate of anaerobic energy release as a result of high-intensity versus low-intensity interval training
A high intensity training group (1,800 m/day at 80% of maximum 200 m time - 90% VO2max) and low intensity training group (1,800 m/day at 70% of maximum 200 m time - 80% VO2max) were compared. The high intensity group exhibited specific anaerobic adaptations: 1. nearly twice as high anaerobic qualities; 2. greater rates of anaerobic energy release capacities; 3. an ability to use muscle glycogen stores at faster rates; 4. an ability to maintain a high percent of maximal anaerobic power during the interval; 5. higher rates of ATP delivery; 6. high blood lactates; and 7. lower pH and base excess data. Implication: Training must incorporate anaerobic sets if rates of energy use are to be improved. A significant factor in sprinting is the ability to mobilize high levels of energy. Training forms at AN-2 level develop this capacity. (ICAR 1990-91 Report)